The Role of Atypical Protein Kinase C in CSF-1-Dependent Erk Activation and Proliferation in Myeloid Progenitors and Macrophages - Lee, Angel W. (PLOS ONE, 2011)
Colony stimulating factor-1 (CSF-1 or M-CSF) is the major physiological regulator of the proliferation, differentiation and survival of cells of the mononuclear phagocyte lineage. CSF-1 binds to a receptor tyrosine kinase, the CSF-1 receptor (CSF-1R). Multiple pathways are activated downstream of the CSF-1R; however, it is not clear which pathways regulate proliferation and survival. Here, we investigated the role of atypical protein kinase Cs (PKCζ) in a myeloid progenitor cell line that expressed CSF-1R (32D.R) and in primary murine bone marrow derived macrophages (BMMs). In 32D.R cells, CSF-1 induced the phosphorylation of PKCζ and increased its kinase activity. PKC inhibitors and transfections with mutant PKCs showed that optimal CSF-1-dependent Erk activation and proliferation depended on the activity of PKCζ. We previously reported that CSF-1 activated the Erk pathway through an A-Raf-dependent and an A-Raf independent pathway (Lee and States, Mol. Cell. Biol. 18, 6779). PKC inhibitors did not affect CSF-1 induced Ras and A-Raf activity but markedly reduced MEK and Erk activity, implying that PKCζ regulated the CSF-1-Erk pathway at the level of MEK. PKCζ has been implicated in activating the NF-κB pathway. However, CSF-1 promoted proliferation in an NF-κB independent manner. We established stable 32D.R cell lines that overexpressed PKCζ. Overexpression of PKCζ increased the intensity and duration of CSF-1 induced Erk activity and rendered cells more responsive to CSF-1 mediated proliferation. In contrast to 32D.R cells, PKCζ inhibition in BMMs had only a modest effect on proliferation. Moreover, PKCζ -specific and pan-PKC inhibitors induced a paradoxical increase in MEK-Erk phosphorylation suggesting that PKCs targeted a common negative regulatory step upstream of MEK. Our results demonstrated that CSF-1 dependent Erk activation and proliferation are regulated differentially in progenitors and differentiated cells.